Infrastructure and Ops Superstream. (O'Reilly Media, Inc., 2023)
You've got your Kubernetes cluster up and running. . .so what's next? You can do much more with Kubernetes than just manage containers. These expert-led sessions will show you how. Join us to keep up with Kubernetes. You'll learn practical strategies and techniques (like how to build K8s into your own developer platform and how to use it on a public cloud), get insight into doing serverless on Kubernetes, and get a glimpse of what the future holds for this widely popular tool. What you'll learn and how you can apply it Understand the benefits and pitfalls of working with Kubernetes Learn how tooling can help with multicluster management This live event is for you because... You're a developer who wants to learn more about developer platforms built on top of Kubernetes so that you can have the tools you need when you need them. You want to use Kubernetes to benefit or improve reliability, velocity, security, and more. You want to learn more about MLOps and the Kubernetes tools ecosystem. Recommended follow-up: Read Kubernetes Up and Running, third edition (book) Explore Certified Kubernetes Application Developer (CKAD), second edition (video course) Watch GitOps and Kubernetes (video edition) Read Introducing MLOps (book) Watch Infrastructure and Ops Hour: Platform Engineering with Camille Fournier (video) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.